Support offered to newborns' parents by the nursing team - Christina Fiorini Tosca; Maitê Larini Rimolo; Márcia Koja Breigeiron (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to know the perception of parents of newborns regarding the support received from the nursing team during their child's hospitalization. Methods: prospective study. Sample of 127 mothers and fathers of newborns hospitalized for at least 72 hours in neonatal units of a hospital in the southern region of Brazil. Data collected from May to September 2018 through application of a proposed questionnaire and consultation of medical records. Descriptive and analytical statistics were used. Results: participants were aged 28.2 (SD = 6.8) years, mostly composed of mothers (76.4%), primiparous (51.2%). Full support was declared by 66.0% of participants in the appreciative domain and 65.5% in the instrumental, 51.7% in the informational and 46.2% in the emotional domains. Mothers declared they felt supported mainly in the instrumental (p=0.009) and informational (p=0.039) domains. There was a positive correlation between the emotional, appreciative and informational domains (p<0.001). Conclusion: for most participants, in the informational domain, there was a demand for knowledge provided by the team, inclusion in decisions and encouragement to ask questions; in the emotional, there was concern for wellbeing and attention to anguish. Greater support for parents in the informational and emotional domains must be reinforced with the use of training strategies for the nursing team.